Analysis of Safety Inventory Control on Wiring Harness Components with ABC Analysis, Economic Order Quantity, and Reorder Point Methods at PT XYZ - Setiawan, Muhamad Yusuf; Hati, Shinta Wahyu (Politeknik Negeri Batam, 2023)
PT XYZ is a manufacturing industry that produces wiring harness for suzuki, daihatsu, and toyota products. Supporting materials in the assembly of wiring harness consist is various types. Therefore, controlling material inventory is important to do so that there is no excess inventory or overstock. This type of research is descriptive quantitative with the aim of knowing the value of material use and investment absorption, optimum order quantity, and reorder time. The classification results using the ABC analysis method obtained materials included in group A consist of 3 types of materials with 76,94% usage and 47,0% investment absorption. Group B consists of 4 types of materials with 21,12% usage and 39,2% investment absorption. Group C consists of 7 types of materials with a usage of 1,94% and investment absorption of 13,8%. Based on the EOQ calculation, the optimum ordering value for group A materials varies from 2.909-4.399, and the reorder point or ROP varies from 1.234-2.371. This research is expected to reduce excess inventory or overstock that occurs in the company.